Sulfide-based composite electrolyte material and preparation method and application thereof
The sulfide-based composite electrolyte material is prepared through the casting coating process, which solves the problems of excessive thickness of the sulfide electrolyte layer and high production cost, and realizes a high energy density and safety all-solid lithium-ion battery, suitable for large-scale production.
Patent Information
- Application Number
- CN202310731617.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
The thickness of the sulfide solid electrolyte layer in existing lithium-ion batteries is too large, resulting in a reduced energy density. The traditional tableting process is costly and is not suitable for large-scale production, which affects the safety and application of the battery.
The casting coating process is used to prepare sulfide-based composite electrolyte materials, and the sulfide electrolyte powder is obtained by mechanical ball milling and sintering. The mixed slurry is formed by combining polymer solution, and applied to the fiber web to dry it to obtain a thickness of 20-55μm. sulfide-based composite electrolyte material.
It achieves high room temperature conductivity and good mechanical properties, promotes the practicalization of all-solid-state lithium-ion batteries, reduces production costs, and is suitable for large-scale industrial production.
Smart Images

Figure CN119170861A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel energy storage, and in particular, the present invention relates to a sulfide-based composite electrolyte material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in various fields from portable electronic devices to large-scale energy storage. Safety issues such as leakage, explosion, and fire of flammable organic liquid electrolytes in commercial lithium-ion batteries have severely restricted their practical applications. Solid electrolytes are considered to be the ultimate way to replace conventional organic liquid electrolytes to improve the safety of next-generation high-energy lithium batteries. At the same time, solid electrolytes can inhibit the generation of lithium dendrites during battery cycling, making it possible to use metallic lithium as the negative electrode of the battery, thereby significantly improving the energy density of current lithium batteries.
[0003] Among the many solid electrolytes, sulfide electrolytes have attracted strong attention due to their ultra-high lithium ion conductivity, simple preparation method and close interface contact. The assembly of sulfide-based all-solid-state lithium metal batteries is to construct a lithium metal battery with a sandwich structure by applying high voltage to lithium sheets, electrolyte and positive electrode powders. However, due to the inherent brittle nature of sulfides, the thickness of the electrolyte layer is not less than several hundred microns or even 1mm to avoid cracks in the electrolyte layer and cause battery failure. But the thick electrolyte layer greatly reduces the mass fraction of active materials in the battery system, thereby greatly reducing the energy density of the battery. Therefore, the thickness of the electrolyte layer must be controlled within a small range. Advanced technologies such as pulsed laser deposition and chemical vapor deposition have been used to deposit solid electrolyte films, showing excellent electrochemical properties. However, unfortunately, for the commercial development of solid-state lithium batteries, it is extremely expensive to use thin film deposition technology to obtain thin electrolyte layers, which is difficult to apply on a large scale. In addition, the strength of thin-layer electrolytes is low, which makes it easier to cause structural damage or cracks due to uneven stress during heating or pressurization, affecting the performance of the battery.
[0004] Composite solid electrolytes are considered to be the most promising candidates for obtaining thin electrolyte layers, and are expected to combine the high ionic conductivity of sulfide electrolytes and the flexibility of polymer electrolytes. In particular, high-content ceramic components (sulfide content>50wt%) have attracted widespread attention due to their excellent electrochemical properties and thermal stability. Research on obtaining thin electrolytes by constructing sulfide-based composite electrolytes has made certain progress. Justin and his colleagues prepared a 64μm thick independent film by hot pressing polymers and Li2S-P2S5 sulfide electrolytes, with a sulfide content of up to 80wt% [Advanced materials 2015,43:6922-6927]. Nan et al. prepared an independent composite solid electrolyte membrane with a thickness of 120μm by cold pressing a composite electrolyte powder composed of sulfide and polymer. The battery prepared with this thin composite electrolyte membrane exhibits excellent electrochemical performance and significantly improves the energy density of solid-state lithium metal batteries [EnergyStorage Materials 2020,25:145-153]. However, the traditional cold pressing or hot pressing process has very high requirements for instruments, which significantly increases the production cost of the electrolyte. What's worse, this sheeting process is incompatible with the roll-to-roll process in existing industrial production, which is not conducive to the large-scale preparation of the electrolyte layer, and seriously restricts the practical application of sulfide-based solid-state batteries. Therefore, it is urgent to reduce the thickness of sulfide electrolytes and realize high-energy-density solid-state lithium-ion batteries that can be prepared on a large scale. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiment of the present invention provides a sulfide-based composite electrolyte material and a preparation method and application thereof.
[0006] An embodiment of the present invention provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0007] S1, Li2S and P2S5 are mixed in proportion and then mechanically ball milled to obtain a glass phase;
[0008] S2, sealing the glass phase pressed sheet, and then sintering it to obtain sulfide electrolyte powder;
[0009] S3, dissolving the polymer in a solvent to obtain a polymer solution;
[0010] S4, adding the sulfide electrolyte powder obtained in step S2 to the polymer solution obtained in step S3, and stirring and dispersing to form a mixed slurry;
[0011] S5, coating the mixed slurry on a fiber net, and obtaining the sulfide-based composite electrolyte material after drying.
[0012] In the embodiment of the present invention, a tape casting coating process is adopted to prepare a sulfide-based composite electrolyte material. The process method is simple, low-cost, does not require special process equipment, is convenient and efficient, is not only suitable for large-scale industrial production, but also solves the inherent problem of thick electrolyte layer caused by traditional cold pressing, thereby greatly promoting the improvement of battery safety and energy density. The sulfide-based composite electrolyte material prepared by the process method has both high lithium ion conductivity and good mechanical properties, laying a foundation for its application in energy storage fields such as all-solid-state lithium ion batteries.
[0013] In some embodiments, in step S1, the molar ratio of Li2S to P2S5 is (70-80):(20-30);
[0014] And / or, the rotation speed of the mechanical ball mill is 450-650 rpm, and the ball milling time is 20-35 h.
[0015] In some embodiments, in step S2, the pressure of the tableting and tube sealing is 110-190 MPa;
[0016] And / or, the heating rate of the sintering treatment is 5-10°C / min; the sintering temperature is 200-600°C, preferably 240-300°C; and the sintering time is 1.5-2.5h.
[0017] In some embodiments, in step S2, the general formula of the sulfide electrolyte powder is (100-x)Li2S-xP2S5, wherein 20≤x≤30;
[0018] And / or, the particle size of the sulfide electrolyte powder is 1 to 15 μm.
[0019] In some embodiments, in step S3, the polymer includes at least one of polyacrylonitrile, polyethylene oxide, polymethyl ethylene carbonate, and polyvinylidene fluoride-hexafluoropropylene, preferably polyethylene oxide; and the solvent is anisole.
[0020] In some embodiments, the polymer accounts for 3 wt % to 5 wt % of the total mass of the sulfide-based composite electrolyte material.
[0021] In some embodiments, in step S5, the fiber web comprises at least one of a polyester web, a nylon web, an acrylic web and a chloroprene web, preferably a nylon web;
[0022] And / or, the drying method is vacuum drying, the vacuum drying temperature is 50-130° C., and the drying time is 3-12 hours.
[0023] On the other hand, an embodiment of the present invention further provides a sulfide-based composite electrolyte material, and the sulfide-based composite electrolyte material is prepared by the above method.
[0024] In some embodiments, the thickness of the sulfide-based composite electrolyte material is 20-55 μm.
[0025] The sulfide-based composite electrolyte material in the embodiment of the present invention has both high room temperature conductivity and good mechanical properties, and when used as the electrolyte layer of an all-solid-state lithium-ion battery, it exhibits excellent electrochemical properties, which greatly promotes the practical application of all-solid-state lithium-ion batteries assembled based on sulfide electrolytes.
[0026] Another aspect of the embodiments of the present invention further provides an all-solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a composite electrolyte layer, wherein the composite electrolyte layer is the above-mentioned sulfide-based composite electrolyte material.
[0027] The advantages and beneficial effects of the present invention are:
[0028] (1) The present invention adopts a tape casting coating process to prepare a sulfide-based composite electrolyte material, which not only solves the problem of an excessively thick electrolyte layer caused by a sulfide electrolyte through a tabletting process, but can also be widely used in the preparation of high-energy-density all-solid-state lithium-ion batteries. In addition, the process is simple, easy to operate, does not require special process equipment, is low in cost, convenient and efficient, and has a wide range of applications.
[0029] (2) The sulfide-based composite electrolyte material in the present invention has both high room temperature electrical conductivity and good mechanical properties, and when used as the electrolyte layer of an all-solid-state lithium-ion battery, it exhibits excellent electrochemical properties, which greatly promotes the practical application of all-solid-state lithium-ion batteries assembled based on sulfide electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the XRD diagram of the sulfide electrolyte powder in Example 1 of the present invention.
[0031] Figure 2 This is a SEM image of the sulfide-based composite electrolyte material prepared in Example 1 of the present invention.
[0032] Figure 3 This is a stress-strain curve diagram of the sulfide-based composite electrolyte material prepared in Example 1 of the present invention.
[0033] Figure 4 This is a cycle performance diagram of an all-solid-state lithium-ion battery assembled using the sulfide-based composite electrolyte material of Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0035] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by those having ordinary skills in the field to which the present invention belongs.
[0036] In this article, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0037] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0038] An embodiment of the present invention provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0039] S1, Li2S and P2S5 are mixed in proportion and then mechanically ball milled to obtain a glass phase;
[0040] S2, sealing the glass phase pressed sheet, and then sintering it to obtain sulfide electrolyte powder;
[0041] S3, dissolving the polymer in a solvent to obtain a polymer solution;
[0042] S4, adding the sulfide electrolyte powder obtained in step S2 to the polymer solution obtained in step S3, stirring and dispersing to form a mixed slurry;
[0043] S5, coating the mixed slurry on a fiber net, and obtaining a sulfide-based composite electrolyte material after drying.
[0044] In the embodiment of the present invention, the sulfide-based composite electrolyte material is prepared by adopting a tape casting coating process, which not only solves the problem of the sulfide electrolyte resulting in an excessively thick electrolyte layer through the tableting process, but can also be widely used in the preparation of high-energy-density all-solid-state lithium-ion batteries. The process method is simple, easy to operate, does not require special process equipment, is low-cost, convenient and efficient.
[0045] In some specific embodiments, in step S1, the molar ratio of Li2S to P2S5 is (70-80):(20-30), non-limiting examples include: 70:20, 70:30, 75:25, 80:20, 80:30, etc.
[0046] In some specific embodiments, in step S1, the rotation speed of the mechanical ball mill is 450-650 rpm, non-limiting examples include: 450 rpm, 500 rpm, 520 rpm, 600 rpm, 650 rpm, etc.; the ball milling time is 20-35 h, non-limiting examples include: 20 h, 25 h, 30 h, 32 h, 35 h, etc.
[0047] In some specific embodiments, in step S2, the pressure for tableting and sealing the tube is 110-190 MPa, non-limiting examples include: 110 MPa, 120 MPa, 150 MPa, 180 MPa, 190 MPa, etc.
[0048] In some specific embodiments, in step S2, the heating rate of the sintering process is 5-10°C / min, non-limiting examples include: 5°C / min, 8°C / min, 10°C / min, etc.;
[0049] And / or, the sintering temperature is 200-600°C, non-limiting examples include: 200°C, 260°C, 350°C, 420°C, 500°C, 600°C, etc.; further, the sintering temperature is preferably 240-300°C, non-limiting examples include: 240°C, 260°C, 280°C, 300°C, etc.;
[0050] And / or, the sintering time is 1.5 to 2.5 hours, non-limiting examples include: 1.5 hours, 1.8 hours, 2.0 hours, 2.2 hours, 2.5 hours, etc.
[0051] In some specific embodiments, in step S2, the general formula of the sulfide electrolyte powder is (100-x)Li2S-xP2S5, wherein 20≤x≤30, for example, the sulfide electrolyte powder can be 80Li2S-20P2S5, 75Li2S-25P2S5, Li3PS4, Li7P3S 11 wait;
[0052] And / or, the particle size of the sulfide electrolyte powder is 1 to 15 μm, non-limiting examples include: 1 μm, 3 μm, 5 μm, 6 μm, 8.5 μm, 10 μm, 12 μm, 15 μm, etc.
[0053] In some specific embodiments, in step S3, the polymer includes at least one of polyacrylonitrile, polyethylene oxide, polymethyl ethylene carbonate, and polyvinylidene fluoride-hexafluoropropylene, preferably polyethylene oxide; and the solvent is anisole.
[0054] In some specific embodiments, in step S4, the polymer accounts for 3wt% to 5wt% of the total mass of the sulfide-based composite electrolyte material, non-limiting examples include: 3wt%, 3.5wt%, 4wt%, 5wt%, etc.
[0055] In some specific embodiments, in step S5, the fiber web comprises at least one of a polyester web, a nylon web, an acrylic web and a chloroprene web, preferably a nylon web;
[0056] And / or, the drying method is vacuum drying, the vacuum drying temperature is 50-130°C, non-limiting examples include: 50°C, 80°C, 100°C, 120°C, 130°C, etc.; the drying time is 3-12h, non-limiting examples include: 3h, 5h, 8h, 10h, 12h, etc.
[0057] On the other hand, the embodiment of the present invention also proposes a sulfide-based composite electrolyte material, which is prepared by the above method. The sulfide-based composite electrolyte material has both high room temperature conductivity and good mechanical properties, and when used as an electrolyte layer of an all-solid-state lithium-ion battery, it exhibits excellent electrochemical properties, which greatly promotes the practical application of all-solid-state lithium-ion batteries assembled based on sulfide electrolytes.
[0058] In some specific embodiments, the thickness of the sulfide-based composite electrolyte material is 20-55 μm, non-limiting examples include 20 μm, 25 μm, 30 μm, 36 μm, 40 μm, 50 μm, 52 μm, 55 μm, etc.
[0059] Another aspect of the embodiments of the present invention further provides an all-solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a composite electrolyte layer, wherein the composite electrolyte layer is the above-mentioned sulfide-based composite electrolyte material.
[0060] The technical scheme of the present invention is further described in detail below in conjunction with specific examples. Conventional instruments and equipment in the art are used in the following examples. The experimental methods without specific conditions in the examples are conventional methods and conventional conditions well known in the art, or methods and conditions recommended by manufacturers. Unless otherwise specified, the various raw materials used in the following examples are conventional commercial products, or can be prepared by known methods.
[0061] Example 1
[0062] This embodiment provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0063] S1, Li2S and P2S5 were mixed in a molar ratio of 70:30, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0064] S2, under a pressure of 150Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 260°C at a heating rate of 5°C / min, and sintered for 2h to obtain a sulfide electrolyte powder Li7P3S with a particle size of 5μm 11 , its XRD pattern is as follows Figure 1 As shown;
[0065] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0066] S4, the sulfide electrolyte powder Li7P3S obtained in step S2 11 Adding to the polymer solution obtained in step S3, stirring and dispersing to form a uniform mixed slurry;
[0067] S5, coating the mixed slurry on a nylon mesh, and vacuum drying at 120° C. for 5 h to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 49 μm.
[0068] Figure 2 is the SEM image of the sulfide-based composite electrolyte material prepared in this embodiment. Figure 2 It can be seen that the polymer is uniformly distributed in the sulfide-based composite electrolyte.
[0069] Figure 3 is a stress-strain curve of the sulfide-based composite electrolyte material obtained in this embodiment. Figure 3 It can be seen that the sulfide-based composite electrolyte material prepared in this embodiment exhibits excellent mechanical properties.
[0070] The sulfide-based composite electrolyte material prepared in this embodiment is used as the composite electrolyte layer, and sulfur is selected as the positive electrode and metallic lithium is selected as the negative electrode to assemble an all-solid-state lithium-ion battery. The cycle performance test results of the battery are as follows: Figure 4 As shown. Figure 4 It can be seen that the all-solid-state lithium-ion batteries made of sulfide-based composite electrolyte materials exhibit excellent electrochemical properties.
[0071] Example 2
[0072] This embodiment provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0073] S1, Li2S and P2S5 were mixed evenly in a molar ratio of 80:20, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0074] S2, under a pressure of 150Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 260°C at a heating rate of 5°C / min, and sintered for 2h to obtain a sulfide electrolyte powder 80Li2S-20P2S5 with a particle size of 6μm;
[0075] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0076] S4, adding the sulfide electrolyte powder 80Li2S-20P2S5 obtained in step S2 to the polymer solution obtained in step S3, and stirring and dispersing to form a uniform mixed slurry;
[0077] S5, coating the mixed slurry on a nylon mesh, and vacuum drying at 120° C. for 5 h to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 52 μm.
[0078] Example 3
[0079] This embodiment provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0080] S1, Li2S and P2S5 were mixed evenly in a molar ratio of 75:25, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0081] S2, under a pressure of 150Mpa, the refined glass phase is pressed into a tube and sealed; then it is placed in a muffle furnace, heated to 260°C at a heating rate of 5°C / min, and sintered for 2h to obtain sulfide electrolyte powder Li3PS4 with a particle size of 6μm;
[0082] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0083] S4, adding the sulfide electrolyte powder Li3PS4 obtained in step S2 to the polymer solution obtained in step S3, and stirring and dispersing to form a uniform mixed slurry;
[0084] S5, coating the mixed slurry on a nylon mesh, and vacuum drying at 120° C. for 5 h to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 51 μm.
[0085] Example 4
[0086] This embodiment provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0087] S1, Li2S and P2S5 were mixed evenly in a molar ratio of 73:27, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0088] S2, under a pressure of 180Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 300°C at a heating rate of 5°C / min, and sintered for 2h to obtain a sulfide electrolyte powder 73Li2S-27P2S5 with a particle size of 3μm;
[0089] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0090] S4, adding the sulfide electrolyte powder 73Li2S-27P2S5 obtained in step S2 to the polymer solution obtained in step S3, and stirring and dispersing to form a uniform mixed slurry;
[0091] S5, coating the mixed slurry on a nylon mesh, and vacuum drying at 120° C. for 5 h to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 20 μm.
[0092] Example 5
[0093] This embodiment provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0094] S1, Li2S and P2S5 were mixed evenly in a molar ratio of 76:24, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0095] S2, under a pressure of 180Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 290°C at a heating rate of 6°C / min, and sintered for 2h to obtain a sulfide electrolyte powder 76Li2S-24P2S5 with a particle size of 4μm;
[0096] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3.5 wt % of the total mass of the sulfide-based composite electrolyte material);
[0097] S4, adding the sulfide electrolyte powder 76Li2S-24P2S5 obtained in step S2 to the polymer solution obtained in step S3, and stirring and dispersing to form a uniform mixed slurry;
[0098] S5, coating the mixed slurry on a nylon mesh, and vacuum drying at 120° C. for 5 h to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 28 μm.
[0099] Comparative Example 1
[0100] This comparative example provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0101] S1, Li2S and P2S5 were mixed in a molar ratio of 70:30, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0102] S2, under a pressure of 150Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 260°C at a heating rate of 5°C / min, and sintered for 2h to obtain a sulfide electrolyte powder Li7P3S with a particle size of 5μm 11 ;
[0103] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0104] S4, the sulfide electrolyte powder Li7P3S obtained in step S2 11 Adding to the polymer solution obtained in step S3, stirring and dispersing to form a uniform mixed slurry;
[0105] S5, coating the mixed slurry on glass, and vacuum drying at 120° C. for 5 hours to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 90 μm.
[0106] Comparative Example 2
[0107] This comparative example provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0108] S1, Li2S, P2S5 and SnS2 were mixed in a molar ratio of 5:1:1, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0109] S2, under a pressure of 150Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 260°C at a heating rate of 5°C / min, and sintered for 2h to obtain a sulfide electrolyte powder Li with a particle size of 5μm 10 SnP2S 12 ;
[0110] S3, dissolving polyethylene oxide in anisole to obtain a polymer solution (wherein the polyethylene oxide accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0111] S4, the sulfide electrolyte powder Li obtained in step S2 10 SnP2S 12 Adding to the polymer solution obtained in step S3, stirring and dispersing to form a uniform mixed slurry;
[0112] S5, coating the mixed slurry on glass, and vacuum drying at 120° C. for 5 hours to remove residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 65 μm.
[0113] Comparative Example 3
[0114] This comparative example provides a method for preparing a sulfide-based composite electrolyte material, comprising the following steps:
[0115] S1, Li2S and P2S5 were mixed in a molar ratio of 70:30, and then mechanically ball-milled at a speed of 520 rpm for 25 h to obtain a glass phase, and the glass phase was ground into fine particles using a mortar;
[0116] S2, under a pressure of 150Mpa, the refined glass phase was pressed into a tube and sealed; then it was placed in a muffle furnace, heated to 260°C at a heating rate of 5°C / min, and sintered for 2h to obtain a sulfide electrolyte powder Li7P3S with a particle size of 5μm 11 ;
[0117] S3, dissolving polymethyl methacrylate in anisole to obtain a polymer solution (wherein the polymethyl methacrylate accounts for 3 wt % of the total mass of the sulfide-based composite electrolyte material);
[0118] S4, the sulfide electrolyte powder Li7P3S obtained in step S2 11Adding to the polymer solution obtained in step S3, stirring and dispersing to form a uniform mixed slurry;
[0119] S5, coating the mixed slurry on a nylon mesh, and vacuum drying at 120° C. for 5 hours to remove the residual solvent, thereby obtaining a sulfide-based composite electrolyte material having a thickness of 60 μm.
[0120] The conductivity test was performed on the sulfide-based composite electrolyte materials prepared in Examples 1-5 of the present invention and Comparative Examples 1-3. The test results are shown in Table 1.
[0121] Table 1
[0122]
[0123]
[0124] It can be seen from Table 1 that, compared with Comparative Examples 1-3, the sulfide-based composite electrolyte materials prepared in Examples 1-5 of the present invention are not only thinner in thickness, but also have higher ionic conductivity, and are expected to be widely used in high energy density and high safety all-solid-state lithium-ion batteries.
[0125] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0126] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a sulfide-based composite electrolyte material, characterized in that: The steps include: S1, Li2S and P2S5 are mixed in proportion and then mechanically ball milled to obtain a glass phase; S2, sealing the glass phase pressed sheet, and then sintering it to obtain sulfide electrolyte powder; S3, dissolving the polymer in a solvent to obtain a polymer solution; S4, adding the sulfide electrolyte powder obtained in step S2 to the polymer solution obtained in step S3, and stirring and dispersing to form a mixed slurry; S5, coating the mixed slurry on a fiber net, and obtaining the sulfide-based composite electrolyte material after drying.
2. The method for preparing a sulfide-based composite electrolyte material according to claim 1, characterized in that: In the step S1, the molar ratio of Li2S to P2S5 is (70-80):(20-30); And / or, the rotation speed of the mechanical ball mill is 450-650 rpm, and the ball milling time is 20-35 h.
3. The method for preparing a sulfide-based composite electrolyte material according to claim 1, characterized in that: In step S2, the pressure of the tableting and tube sealing is 110-190 MPa; And / or, the heating rate of the sintering treatment is 5-10°C / min, the sintering temperature is 200-600°C, and the sintering time is 1.5-2.5h.
4. The method for preparing a sulfide-based composite electrolyte material according to claim 1, characterized in that: In the step S2, the general formula of the sulfide electrolyte powder is (100-x)Li2S-xP2S5, wherein 20≤x≤30; And / or, the particle size of the sulfide electrolyte powder is 1 to 15 μm.
5. The method for preparing a sulfide-based composite electrolyte material according to claim 1, characterized in that: In the step S3, the polymer includes at least one of polyacrylonitrile, polyethylene oxide, polymethyl ethylene carbonate, and polyvinylidene fluoride-hexafluoropropylene; and the solvent is anisole.
6. The method for preparing a sulfide-based composite electrolyte material according to claim 5, characterized in that: The polymer accounts for 3 wt % to 5 wt % of the total mass of the sulfide-based composite electrolyte material.
7. The method for preparing a sulfide-based composite electrolyte material according to claim 1, characterized in that: In the step S5, the fiber web comprises at least one of a polyester web, a nylon web, an acrylic web and a chloroprene web; And / or, the drying method is vacuum drying, the vacuum drying temperature is 50-130° C., and the drying time is 3-12 hours.
8. A sulfide-based composite electrolyte material, characterized in that: The sulfide-based composite electrolyte material is prepared by the method according to any one of claims 1 to 7.
9. The sulfide-based composite electrolyte material according to claim 8, characterized in that: The thickness of the sulfide-based composite electrolyte material is 20 to 55 μm.
10. An all-solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a composite electrolyte layer, characterized in that: The composite electrolyte layer is a sulfide-based composite electrolyte material prepared by the method according to any one of claims 1 to 7 or a sulfide-based composite electrolyte material according to claim 8 or 9.
